Identification of inactive conformation‐selective interleukin‐2‐inducible T‐cell kinase (ITK) inhibitors based on second‐harmonic generation. Issue 9 (30th July 2018) - Hantani, Yoshiji; Iio, Kiyosei; Hantani, Rie; Umetani, Kayo; Sato, Toshihiro; Young, Tracy; Connell, Katelyn; Kintz, Sam; Salafsky, Joshua
Abstract : Many clinically approved protein kinase inhibitors stabilize an inactive conformation of their kinase target. Such inhibitors are generally highly selective compared to active conformation inhibitors, and consequently, general methods to identify inhibitors that stabilize an inactive conformation are much sought after. Here, we have applied a high‐throughput, second‐harmonic generation (SHG)‐based conformational approach to identify small molecule stabilizers of the inactive conformation of interleukin‐2‐inducible T‐cell kinase (ITK). A single‐site cysteine mutant of the ITK kinase domain was created, labeled with an SHG‐active dye, and tethered to a supported lipid bilayer membrane. Fourteen tool compounds, including stabilizers of the inactive and active conformations as well as nonbinders, were first examined for their effect on the conformation of the labeled ITK protein in the SHG assay. As a result, inactive conformation inhibitors were clearly distinguished from active conformation inhibitors by the intensity of SHG signal. Utilizing the SHG assay developed with the tool compounds described above, we identified the mechanism of action of 22 highly selective, inactive conformation inhibitors within a group of 105 small molecule inhibitors previously identified in a high‐throughput biochemical screen. We describe here the first use of SHG for identifying and classifying inhibitors that stabilize an inactive vs. an active conformation of a protein kinase, without the need to determine costructures by X‐ray crystallography. Our results suggest broad applicability to other proteins, particularly with single‐site labels reporting on specific protein movements associated with selectivity. Abstract : There is great demand for identifying inhibitors that stabilize the inactive conformation of protein kinases. In this study, we used a second‐harmonic generation (SHG)‐based approach to identify stabilizers of the inactive conformation of interleukin‐2‐inducible T‐cell kinase and found highly selective, inactive conformation inhibitors. Our results suggest SHG offers a valuable, high‐throughput approach for identifying inactive conformation inhibitors of protein kinases.